Integrating environmental concerns in the operations of the Philippine Army's 7th infantry division in Fort Magsaysay - Rodil, Rolando R. (2007)
War is said to have its costs. It takes its toll on lives, on peoples, on nations. But what we often take for granted is that war, and the preparations to go war, has a greater cost-and impact-on the natural environment. The military, as an institution and as an organization, has a similar environmental responsibility to mitigate these impacts. Every operation and activity of units in 7ID has its attendant environmental aspects-those that would "interact" with the environment. Subsequently, these particular aspects of the operation have its own environmental impacts (or consequences, or "effects". Whether in the office or in the motor pool, whether one is working at a construction project or in the hospital, in combat operations or in field training exercises, there are significant environmental aspects and impacts. Chapter 4 outlined several key impacts such as on the effective management of solid and hazardous wastes as well as air and water quality issues resulting from the operations and activities of 71D units in Fort Magsaysay.
"July 11, 2006."
Thesis (M.A. Urban and Regional Planning)--University of the Philippines Diliman.
Keywords: Environmental policy -- Philippines